Intercropping of chickpea and Indian mustard for resource conservation and production in Bundelkhand region in Central India - Narayan, Dev (Indian Farming, 2019)
Intercropping of chickpea and Indian mustard (8:1)in terms of chickpea equivalent yield for bothcrops (chickpea + Indian mustard) revealed that total production and net returns were observedhigher with intercropping over sole cropping of chickpea in Bundelkhand region in Central. Thewater use efficiency also increased under intercropping over sole cropping of chickpea.